THE CORRELATION BETWEEN STUDENTSâ€™ MOTIVATION AND ENGLISH LEARNING ACHIEVEMENT - Tiara, Ega; Supardi, Iwan; Salam, Uray (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to observe the correlation between studentsâ€™ motivation and their English learning achievement at the Eighth grade of SMP Negeri 2 Sambas in academic year 2016/2017. The sample of this study was the 38 students in class VIIIA. The English learning achievement in this study refers to the studentsâ€™ English learning score. Based on the aim of the research, the researcher formulated study with correlational study. The studentsâ€™ motivation score was obtained from questionnaire administered in the class. The questionnaire consisted of 20 items. This questionnaire was adopted from Gardnerâ€™s AMTB about motivation questionnaire for learners. For the studentsâ€™ English learning score, the researcher got it through documentation from the English teacher. This English learning score was obtained from the studentsâ€™ midterm test. In analyzing the data, the researcher used Pearson Product Moment in the program SPSS 16. The result from the calculation showed that the value of is -0.26. The researcher then compared it with at the significant degree 5% (0.355), the correlation between studentsâ€™ motivation and their English learning achievement is negative ( : = -0.26 < 0.355). As a result, the alternative hypothesis which states that â€œthere is correlation between X variable and Y variableâ€ is rejected.Â Keywords: Correlation, Studentsâ€™ motivation, English Language Achievement